Biocomposite of Hydroxyapatite from Chicken Egg Shells and Biochar from Rice Husk As an Adsorbent for Copper Ion and Methylene Blue - hendri setiawan; Umi F. Anindi; Dedek Y Pulungan; Nur Akbar; Atiek R. Noviyanti; Solihudin Solihudin (Jurnal Keramik dan Gelas Indonesia, 2020)
The growth of industrial activity and increasing use of water have effected to the releasing of various pollutants into the waters, as methylene blue and copper ions. Excess levels of methylene blue and copper ions in the waters can cause ecosystem damage. This study aims to obtain biocomposites of hydroxyapatite from chicken egg shells and biochar from rice husk as well as their adsorption ability to inorganic pollutants (Cu (II)) and organic pollutant (methylene blue). Hydroxyapatite (HA) was synthesized by calcining chicken eggshells into CaO powder which is then reacted with (NH4)2HPO4. Furthermore HA was mixed with biochar from rice husk to form biocomposites. The ability of the biocomposite adsorption test was carried out by varying the time and initial concentration of the metal solution and methylene blue. Based on the results of the study, HA-biochar composites showed the best contact adsorbing time for methylene blue and copper ions 50 and 30 minutes respectively. Testing of biocomposite adsorption ability to the initial concentration of methylene blue as much as 12.79 ppm showed that the biocomposite is able to adsorb methylene blue to a residual concentration of 1.15 ppm or the maximum percentage of methylene blue that can be adsorbed by 91%. The ability of HA-biochar composites to adsorb methylene blue is better than its constituent materials (HA and biochar). HA-biochar composites was also able to adsorb Cu ions with an average adsorption percentage of 79.45% from the initial concentration.